The Growth of Lemna Minor and Pistia Stratiotes in Batulayang Landfill’s Leachate - Perdana, Aurendyo Yuscel; Zakiah, Zulfa; Rusmiyanto, Elvi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Lemna minor and Pistia stratiotes are plants that can be used to degrade haevy metal pollutants iron (Fe) and lead (Pb) present in aquatic environments and can imprave water quality. The purporse of this study was to determine the best combination between L. minor and P. stratiotes in improving leachate water quality. This study uses a Completely Randomized Design (CRD) with five treatment levels with 3 replications each. The data obtained were then analyzed using descriptive.The results showed that the best plant combination in improving leachate water quality and capable of absorbing heavy metals iron and lead was L1P3 with a percentage reduction of heavy metals iron and lead of 98,2% and 85 % respectively as a result L. minor and P. stratiotes after treatment on Batu Layang Landfill leachate experienced an increase in biomass and chlorophyll content, as well as being able to reduce lead and iron levels. The results of this study are in line with Minister of Environment Regulation of the Republic of Indonesia Number 59 of 2016 concerning quality standards for leachate from business premises or final disposal sites.